A Framework based on a Pattern Language for Business Resource Management - Braga, Rosana T. Vaccare; Masieiro, Paulo Cesar (Anais Estendidos do Simpósio Brasileiro de Engenharia de Software (SBES), 2000)
A framework based on a pattern language for Business Resource Management is under construction to be used for developing systems in the information systems domain. Business resources include assets and services, as products and repairs. By management we mean their trade, rental and maintenance. A pattern language has been developed for aiding in the analysis of systems for business resource management. It includes fourteen patterns for identifying the resource, quantifying it, renting, trading and maintaining it, reserve it, quote the trade, quote the maintenance, check its delivery, allowing several items to be dealt with in the same transaction, paying for the transaction, identifying the transaction executor, and identifying maintenance tasks and parts. One of the patterns is included, corresponding to trading the resource. A class model shows its structure (classes and relationships), and an application example shows the roles played by each participant class. An example of the pattern language usage for a car repair shop system is presented, together with an object model that shows the patterns used and the roles played by their participant classes. The present development stage of the framework is mentioned.